Pengembangan Media Flashcard Untuk Pembelajaran Membaca Permulaan Siswa Kelas I - Titingganur, Helda; Pasassung, Nikolaus; Saputra, Erwin Eka; Parisu, Chairan Zibar L. (Jurnal Sultra Elementary School, 2025)
Media is an important thing in facilitating the implementation of the learning process in the form of flashcard for beginning reading of grade 1 students at SDN 4 Maligano, totaling 25 people. This research and development ( Research and Development RD ) which uses the ADDIE stages. The results of this research are products in the form of flashcard media. The product specifications produced are in the form of A4 sized print cards using ivory art paper with a thickness of 250 gsm. This flashcard was created using the canva application. The contents of the material flashcard media include the title of the material, the main discussion point of the material, and supporting images. The flashcard media in this research explains that the flashcard studied are suitable for use.